LES FACTEURS DE MOTIVATION DU PERSONNEL DU SECTEUR PRIVE : UNE REFLEXION A PARTIR DE LA GESTION DES CARRIERES A LA SOCIETE IVOIRIENNE DE BANQUE - Gacha, Franck-Gautier (European Scientific Journal, ESJ, 2015)
In an organization, there are various resources that contribute to its optimal functioning. Of all resources, the human factor is presented in the form of a significant element for achieving the objectives set by the organization. It is in this light that is set up a HRM policy which covers several aspects including payroll, personnel administration, career management, recruitment, training, conflict management, social consultation. This article aims at showing the influence of career management on workers' motivation, from the case of employees of Société Ivoirienne de Banque. The general assumption is that the motivation of workers is partly linked to the effective career management mode in this organization. The methodological approach is summarized in the documentation and semistructured individual interviews realized with employees of SIB, chosen accidentally. The results show that the needs faced by the employer are to make the company productive, competitive and generate profits. Thus, career management (included in the policy HRM) appears as an asset to SIB, as a key factor in maximizing its profits. The better the career profile is known and readable, the better the worker is motivated and is involved in his work.